Analysis and characterization of dynamic recrystallization and grain structure evolution in friction stir welding of aluminum plates. (1st April 2021) - Yu, Pengfei; Wu, ChuanSong; Shi, Lei
Abstract: The dynamic recrystallization (DRX) process and grain structure evolution during friction stir welding determine the final microstructure and performance of weld joints. In this study, Monte Carlo method is applied to develop a model for numerical simulation of dynamic recrystallization in friction stir welding of aluminum plates. An appropriate DRX nucleation model suitable for Monte Carlo simulation is selected, and the correlation of the Monte Carlo simulation step and the real time is calibrated. The transient evolution and the final distribution of grain structures in welds are predicted numerically. The calculated grain sizes in weld nugget zone are in good agreement with the experimentally measured ones. The dynamic recrystallization mechanism during friction stir welding of 1060 aluminum plate is analyzed by combining the finite element simulation and Monte Carlo simulation results with the characterization results of electron backscatter diffraction. It is found that along the material flowing path during friction stir welding, the main DRX mechanisms are different at leading, retreating and trailing sides around the tool, and the tool rotation speed (associated with the heat input level) determines which type of DRX is easier to occur at different positions along material flowing path. Graphic abstract: Image, graphical abstract